Doing social work research - Smith, Roger (Open University Press, 2009)
This accessible book is based on the author's extensive practical experience of carrying out and teaching research in the social work field. Social work research is shown to be both a distinctive academic enterprise and a task that can be accomplished effectively in line with the values and ethical principles that lie at the discipline's core